The History of the Chemo-Free Model in the Treatment of Acute Promyelocytic Leukemia - Zhu, Hong-Hu (Frontiers in Oncology, 2020)
Acute promyelocytic leukemia (APL) now becomes a highly curable disease after four decades endeavors. Thanks for investigators from all the world, a chemo-free concept has become reality not only in low-risk, even in high-risk patients. All-trans retinoic acid (ATRA) plus arsenic trioxide (ATO) without chemotherapy become first-line treatment for newly diagnosed APL, which had adopted in guidelines or expert recommendations from NCCN, ELN, and China. Though great success, challenges still exist. The rate of early death still has not diminished significantly and is a major obstacle to cure all the patients. Leukocytosis is the most important factor for ED and completely abandon chemotherapy is dangerous for certain patients in practice. To narrow the gap between the guidelines and practice, this review tries to examine history of chemo-free model for treatment of APL in arsenic alone era (1974-2002) and arsenic plus ATRA era(2002~present), and provide practical considerations about early death.